Credit union correspondents and financial inclusion in Brazil: an exploratory study - Kalliala, Oskari (2016)
The Brazilian banking correspondent network has been a topic of study for already a decade, due to its well-documented success in improving access to financial services in remote areas. The marginal but growing role of credit unions in the usage of correspondents has not received much attention from academics, despite the appraised importance of credit unions in finance of proximity. This thesis takes a multi-method approach to perform an exploratory research of credit union correspondents in Brazil. The research objective is two-fold, aiming, from one side, at understanding the incentives of credit unions for contracting correspondents and, from the other, at evaluating whether credit union correspondents improve financial inclusion. The research consists of a case study and quantitative analysis of correspondent registration data and credit union financials. The results indicate that generally the largest and most profitable credit unions use banking correspondents in order to improve efficiency and decrease waiting lines, while promoting financial inclusion only in one restricted dimension – bill payment. Nevertheless, in 2014, credit union correspondents had an important role in providing access to payments in 690 municipalities, of which 200 had low financial depth. Despite the scope limitation of credit union correspondents, the results give reasons to believe that these actors could increase their importance in the promotion of financial inclusion in the future.